Single-step, single-organism bioethanol production and bioconversion of lignocellulose waste materials by phlebioid fungal species. (February 2017) - Mattila, Hans; Kuuskeri, Jaana; Lundell, Taina
Graphical abstract: Highlights: Phlebia fungi convert non-pretreated lignocellulose into ethanol and organic acids. Ethanol yield of 0.104 g/g core board solid substrate was achieved. Single-step ethanol production from core board by fungi is enhanced by pH 3. Consolidated bioprocessing of waste lignocellulose into fumarate is potential. Fungal biotechnology is an option for more sustainable use of natural resources. Abstract: Ethanol production from non-pretreated lignocellulose was carried out in a consolidated bioprocess with wood-decay fungi of phlebioid Polyporales. Ethanol production was attempted on glucose, spruce wood sawdust and waste core board. Substantial quantities of ethanol were achieved, and isolate Phlebia radiata 0043 produced 5.9 g/L of ethanol reaching the yield of 10.4% ethanol from core board lignocellulose substrate. Acidic initial culture conditions (pH 3) induced ethanol fermentation compared to the more neutral environment. Together with bioethanol, the fungi were able to produce organic acids such as oxalate and fumarate, thus broadening their capacity and applicability as efficient organisms to be utilized for bioconversion of various lignocelluloses. In conclusion, fungi of Phlebia grow on, convert and saccharify solid lignocellulose waste materials without pre-treatments resulting in accumulation of ethanol and organic acids. These findings will aid in applying fungal biotechnology for production of biofuels and biocompounds.